A multidimensional conceptualization of the sponsor-sponsee fit in sport. Issue 5 (2nd September 2020) - Rajabi, Asieh Ghorbanian; Talebpour, Mahdi; Martinent, Guilllaume; Bodet, Guillaume; Kafashpor, Azar
ABSTRACT: The aims of the study were to identify the most relevant conceptualisation of the factor structure of the sponsor-sponsee fit in sport sponsorship using advanced statistical methods (bifactor model) recently introduced within the literature and examine which dimensions of the sponsor-sponsee fit construct were the strongest predictors of the overall sponsor-sponsee fit construct. A total of 270 participants from Iran completed a questionnaire on three sponsors of the Iranian national volleyball team. Indices-of fit and Yuan-Bentler likelihood ratio tests revealed that a model comprising nine dimensions of fit provided the best fit to the data across the three sponsors. Results of structural equation modelling analyses revealed that the specific dimension of explicitness was the strongest predictor of the overall measure of fit. Theoretical and managerial implications of the present results for the sport marketers have been discussed.